Health Analysis of Bank Syariah Indonesia (BSI) Financial Reports in 2020 and 2021: Analisis Kesehatan Laporan Keuangan Bank Syariah Indonesia (BSI) Tahun 2020 and 2021 - Suwinda Aulansari; Maura Morena Pinka; Chairina (LPPM Institut Studi Islam Sunan Doe, 2022)
Banking financial institutions play an important role in the economy. Public trust is one of the foundations for the success of the banking industry which faces increasingly fierce competition. The need to monitor the level of bank health must be carried out by banks in order to increase public confidence in handling their business finances. Bank financial statements can be researched as one of the sources. The purpose of this study is to measure the level of banking health at Bank Syariah Indonesia. The analytical tool used is RGEC (Risk Profile, Good Corporate Governance, Earning and Capital). The data or information in this study is a bank financial report published from 2020 & 2021. The results of the study prove that the bank is healthy. This is determined using the RGEC approach to evaluation. In this situation, Bank Syariah Indonesia has the potential to have a major adverse impact with changes in the economic climate and other external conditions. In 2020-2021, Bank Syariah Indonesia can also manage the health and stability of Islamic banks.